168k views
0 votes
(-2/5)7÷(-2/5)5=????

User JoG
by
5.3k points

2 Answers

1 vote

Answer:

Step-by-step explanation: So you have to take care of the brackets first (-2/5)7 gives -14/5. (-2/5)5 gives us -10/5. Therefore, we have -14/5 ÷ -10/5. According to the law of division, the sign changes to multiplication with a reciprocal of the divisor so we have -14/5 × -5/10. - × - = +. So we have 70/50. In lowest terms the answer is 7/5.

User Sergio Mendez
by
5.7k points
2 votes

Answer:


(4)/(25)

Explanation:

Using the rule of exponents


a^(m) ÷
a^(n)
a^((m-n))

Given


-2/5)^(7) ÷
(-2/5)^(5)

=
(-2/5)^((7-5))

=
(-2/5)^(2)

= -
(2)/(5) × -
(2)/(5) =
(4)/(25)

User Chronoxor
by
5.3k points